Persistent serum immune complexes in syphilis. Issue 4 (August 1980) - Engel, S; Diezel, W
Abstract : Serum immune complexes were estimated by a polyethylene glycol precipitation method in 51 patients with early syphilis. The immune complexes were increased in 41% of patients before treatment and decreased to normal limits in only 56% during treatment. The results of the specific antireponemal tests using dissolved immune complexes show that antibodies from the immune complexes are specific antibodies.